The Concept of the Social State and its Implementation in the Russian Federation - BAIEVA, Nataliya Anatolyevna; BURKIN, Dmitriy Olegovich; VYSHESLAVOVA, Tatyana Fedorovna; LUKINOVA, Svetlana Alekseevna (Journal of Advanced Research in Law and Economics, 2018)
Abstract: This scientific paper is aimed at the study of the issues related to the implementation of the concept of the Russian social state, proclaimed in Art. 7 of the Constitution of the Russian Federation. The historical prerequisites for the formation of various concepts of the social state and the institutionalization of social human rights are considered in this article using the historical and comparative legal method of study. The right to work is a system-forming social human right, and in this regard, the authors carried out the analysis of the norms of the Russian labor law guaranteeing the implementation of the right to decent work, the right to choose freely the forms and the types of employment, the right to protection against unemployment, the right to exercise a labor function in safe working conditions, and the right to just remuneration for work. Specific measures aimed at achieving the goals of the Russian social state and the implementation of the principle of decent work, based on the labor rights of the citizens, are proposed. The conclusion on the gradual implementation of the idea of the social state in the Russian Federation is drawn.